2017
DOI: 10.2147/blctt.s130826
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of lymphoma-derived exosomes by peripheral blood leukocytes

Abstract: Exosomes are nanosized lipid vesicles secreted into blood and other body fluids and serve as vehicles for intercellular communication. Despite being an important component of the tumor microenvironment (TME), exosomal targeting and uptake into recipient cells are still not fully understood. Few studies have looked at lymphoma exosomes and their interactions with circulating blood cells. In this study, we examine the exosomal uptake distribution among peripheral blood leukocytes (PBLs) using vesicles derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…These heterogeneous protein profiles are specific to each cell type and contribute to the comparative ability of each cell to internalize exosomes. In line with the role of B cells, it was found that they readily take in exosomes, in contrast to other immune cells such as T cells and natural killer cells [61,64]. This suggests that certain immune cells are more effective at endocytosing exosomes than others, consistent with the primary functions of these specific cell types.…”
Section: Cell-specific Internalization Of Exosomes By Antigen Presentmentioning
confidence: 70%
See 1 more Smart Citation
“…These heterogeneous protein profiles are specific to each cell type and contribute to the comparative ability of each cell to internalize exosomes. In line with the role of B cells, it was found that they readily take in exosomes, in contrast to other immune cells such as T cells and natural killer cells [61,64]. This suggests that certain immune cells are more effective at endocytosing exosomes than others, consistent with the primary functions of these specific cell types.…”
Section: Cell-specific Internalization Of Exosomes By Antigen Presentmentioning
confidence: 70%
“…In a peripheral blood mononuclear cell culture, when uptake by monocytes was blocked, internalization by T-cells increased [47], suggesting that T cell uptake may be an adaptive response to increased exosome concentration. When exosome uptake was compared to multiple splenic leukocytes [15] or peripheral blood leukocytes [64], T cells showed minimal internalization. T cell activity is often regulated by surface interactions with other cells, such as with the T cell receptor and the MHC II/antigen interaction with APCs.…”
Section: Circulating Cellsmentioning
confidence: 99%
“…Exosomes were then re-assessed for size and concentration and no alteration to size was observed (data not shown). Exosome uptake has been described to take as little as 1 hour up to 12 hours, with a general plateau effect at 4 hours [ 39 , 47 49 ]. HeLa cells were incubated with these exosomes for 4 hours and then analyzed with flow cytometry or with fluorescent microscopy (Figures 2 - 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…While an effect on NK cell protein was seen with survivin by itself, the effect was lost by dilution into exosomes. Therefore, survivin in the TME sourced from necrosing tumor cells may show more effects than exosomal survivin due either to concentration or uptake issues, as NK cells have not been shown to efficiently uptake exosomes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer (NK) cells were prepared from freshly collected plasma apheresis peripheral blood obtained from healthy donors at the Life Stream Blood Bank (San Bernardino, CA, USA), in accordance with Loma Linda University IRB protocols. Peripheral blood was prepared as described previously [ 47 ]. NK cells were obtained from the total lymphocyte fraction by negative immunomagnetic cell separation using either EasySep or RosetteSep negative selection kit (STEMCELL, Vancouver, BC, USA) or MACS magnetic NK cell isolation kit (Miltenyi Biotec, Auburn, CA, USA).…”
Section: Methodsmentioning
confidence: 99%